MOTIF CERITA RAKYAT SEBAGAI SARANA PENJAGA INTEGRITAS SOSIAL MASYARAKAT ASEAN - Lilik Wahyuni (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Folklore is a traditional story to convey the noble values of a region to the future generations which are delivered using spoken language. The focus of this study are (1) the motifs and variations of Malin Kundang folklore in various ASEAN countries, (2) the function of folklore as the guardian of ASEAN social integrity, and (3) educational value of folklore as the guardian of ASEAN social integrity. This study used a qualitative approach with ethnography of communication design. The main data in this study are the words and actions which are delivered by the speakers used in folklore. The data collection method used in this research is focused observation. The data were analyzed by sorting, selecting, and interpreting the data. Based on the results of data analysis can be concluded that (1) the motif of